Effect of thermal treatment on the morphology of PLZT thin films prepared from polymeric precursor method - González, A. H. M. [UNESP]; Simões, A. Z. [UNESP]; Varela, José Arana [UNESP]; Zaghete, M. A. [UNESP]; Longo, Elson [UNESP] (Trans Tech Publications, 2001)
Lead lanthanum zirconate titanate (PLZT) thin films with (9/65/35) stoichiometry were prepared by dip coating from polymeric precursor method. The films deposited on silicon (100) substrates, were thermally treated from 450° to 700°C for 6 hours in order to study the influence of thermal treatment on the crystallinity, microstructure, grain size and roughness of the final film. X-ray diffraction results showed that PLZT phase crystallizes at low temperature (500°C) and present preferential orientation. It was observed by scanning electron microscopy (SEM) that it is possible to obtain dense thin films at temperatures around 650°C. The atomic force microscopy (AFM) studies showed that the grain size and roughness are strongly influenced by the annealing temperature.
Keywords: Annealing; Atomic force microscopy; Crystal microstructure; Crystal orientation; Grain size and shape; Lead compounds; Scanning electron microscopy; Stoichiometry; Surface roughness; X ray diffraction analysis; Crystallinity; Lead lanthanum zirconate titanate; Thin films